Influence of Important Factors in Hedging Decisions Using Derivative Instruments (Case Study on Automotive Industry Companies Listed on the IDX) - Yusbardini Yusbardini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to analyze the effect ofLiquidity, Growth Opportunity, Firm Size, and Managerial Ownership as factors that influence hedging activities using derivatives in automotive companies listed on the Indonesia Stock Exchange.”The sampling technique used was purposive sampling. The sample in this study amounted to 12 automotive companies that met the criteria. This study uses secondary data sourced from the annual financial statements of automotive companies listed on the Indonesia Stock Exchange for the period 2015 to 2019. Data analysis uses logistic regression because the data used are metric and non-metric. .Results showliquidity (Liquidity),Managerial Ownershipand Size (Firm Size)has a negative and significant effect on hedging activities while the Company's Growth Opportunity has a positive and significant effect on hedging activities using derivatives.